Cegah Stunting dengan Puding Daun Kelor pada Ibu Hamil di Desa Loram Wetan Kudus - Dian Arsanti Palupi; Yulia Pratiwi; Dwi Susiloningrum; Lilis Sugiarti; Annis Rahmawaty; Icha Vidyani Setyana Wati; Ana Dwi Rizkina; Astin Dwi Wardini (Compromise Journal Community Proffesional Service Journal, 2025)
Stunting was growth failure in children caused by chronic malnutrition or infectious disease, resulting in impaired physical and cognitive growth. This community service suggests using Moringa oleifera leaves to prevent stunting by making pudding. Moringa leaves are famous for their high nutritional value, containing vitamins A, C, and E and minerals such as calcium, iron, and protein. This community service program aims to increase the skills and knowledge of the community, especially pregnant women, in making Moringa leaf pudding and the importance of improving nutrition in pregnant women. The method used was descriptive, lecture, discussion and direct practice in making Moringa leaf pudding with village midwives, pregnant women at the posyandu in Loram Wetan Kudus village. The results of this community service activity can be seen from the increase in participants' knowledge and ability to make Moringa leaf pudding correctly according to the instructions that have been given previously. This community service activity concludes that participants can make Moringa leaf pudding independently and increase pregnant women's knowledge about the benefits of Moringa leaves, which are rich in nutrients and can be used to improve nutritional status to reduce the incidence of stunting.